New Seven-Step Numerical Method for Direct Solution of Fourth Order Ordinary Differential Equations - Zurni Omar; John Olusola Kuboye (Institute for Research and Community Services (LPPM) ITB, 2016)
A new numerical method for solving fourth order ordinary differential equations directly is proposed in this paper. Interpolation and collocation were employed in developing this method using seven steps. The use of the approximated power series as an interpolation equation was adopted in deriving the method. The basic properties of the new method such as zero-stability, consistency, convergence and order are established. The numerical results indicate that the new method gives better accuracy than the existing methods when it is applied to fourth ordinary differential equations.